Unravelling the Antioxidant Potential, Alpha-Glucosidase Inhibitory Activity and Phenolic Composition of Dendrocalamus strictus Plantations Generated Biomass Waste (Leaves) - Pande, Himani; Kumar, Brijesh; K. Varshney, Vinay (Natural Products Journal, The, 2016)
Background: Vast quantity of leaves as biomass waste is generated from Dendrocalamus strictus (DS) plantations and may have serious environmental impact from their disposal. One approach for management of this waste is the recovery of valuable compounds for industrial applications. Objective: Antioxidant capacity (AOXC) and α-glucosidase inhibitory activity (GIA) guided chemical examination of the leaves and identification of their phenolic compounds. Methods: Eight extracts were prepared by extracting the fresh and shade dried leaves at room temperature for 72 hrs or Soxhlet extracted for 6 hrs with methanol and methanol: water (4:1. v/v) separately. Total Phenolic Contents (TPCs) and Total Flavonoid Contents (TFCs) were determined using Folin- Ciocalteu and aluminum chloride method, respectively. Antioxidant capacity was ascertained by DPPH• scavenging, reducing power, hydroxyl radical scavenging and metal chelating assays. Phenolic compounds were characterized using HPLC-ESI-QTOF- MS. Results: Hot methanol: water extract of the fresh leaves, being the most active, based on highest yield, TPCs, TFCs and total AOXC was fractionated with petroleum ether, ethyl acetate, butanol and water. Ethyl acetate and butanol fractions were the most potent due to their highest TPCs, TFCs and total AOXC, however, showed weak GIA. 6 phenolic acids, 5 flavones and 1 flavonol with varied distribution in these fractions were characterized. A significant correlation was found between polyphenols and AOXC as well as within the various antioxidant assays. Conclusion: DS leaves could be utilized as a potential natural source of antioxidants for socioeconomic and environmental benefits.
Keywords: biomass waste